O gênero Eugenia: da química à farmacologia - Veloso, Juvenal Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Research on natural products is extremely important either for new compound discovery with possible pharmacology uses or for its impact on economy, which moves millions of dollars for year. Scientific studies related on utilization and characterization of bioactive substances are important due to the fact that many drugs currently used by the population were synthetized from isolated compounds of natural products. Among many medicinal species commonly used, there are that ones from the genus Eugenia, witch belongs to Myrtaceae family. Eugenia is one of the biggest genus from this family and has about 5000 species and Brazil has 400 of them, which are appreciated on gastronomy for its fruits, for example, pitanga (Eugenia uniflora), cherry (Eugenia involucrata), clove (Eugenia caryophyllata) and cagaita (Eugenia dysinterica). Phytochemical studies of plants from this genus report the presence of several secondary metabolites like flavonoids, tannins, coumarins, anthocyanins and more. Eugenia species have important pharmacology activity as antioxidant, hypothermic, antidiarrheal, antihypertensive, antimicrobial and fungicide. Thus, Eugenia is a genus which has species with potencial phytotherapic products

Os estudos de produtos naturais são de extrema importância tanto em relação a descoberta de novos compostos com possíveis utilizações farmacológicas quanto ao seu impacto na economia, o qual move milhões de dólares por ano. Estudos científicos relacionados à utilização e caracterização de substâncias bioativas se fazem importantes devido ao fato de que muitos fármacos utilizados atualmente foram sintetizados a partir de compostos isolados de produtos naturais. Dentre as espécies medicinais muito utilizadas pela população estão as do gênero Eugenia, que pertence a família Myrtaceae. O gênero Eugenia é um dos maiores da família Myrtaceae e compreende aproximadamente 5000 espécies, sendo 400 presentes no Brasil, as quais são apreciadas gastronomicamente devido aos seus frutos, como por exemplo a pitanga (Eugenia uniflora) e a cereja (Eugenia involucrata), cravo-da-Índia (Eugenia caryophyllata), cagaita (Eugenia dysenterica). Estudos fitoquímicos de plantas desse gênero relatam a presença de diversos metabólitos secundários como flavonoides, taninos, cumarinas, antocianinas, entre outros. Espécies de Eugenia possuem atividades farmacológicas importantes como atividade antioxidante, hipotérmica, antidiarreica, antihipertensiva, antimicrobiana e fungicida. Portanto, Eugenia é um gênero que compreende espécies com grandes potenciais para produção de fitoterápicos
Keywords: Química vegetal; Plantas medicinais; Eugênia (Planta); Farmacologia; Laranja - Variedades; Terapias alternativas; Medicina popular; Mudança de hábitos; Botanical chemistry